GELCO: Gamified educational learning contents ontology - Antunes, A.; Lopes, M.; Barateiro, J.; Cardoso, E. (CAPSI 2023 Proceedings, 2023)
Higher education students and teachers lack the necessary information to monitor and analyse student performance with respect to the learning experience and autonomous work during the semester. This research is based on the need for continuous improvement of student learning monitoring for students and teachers. It aims to combine ontologies with a monitoring platform, creating new ways of structuring and visualizing the elements of a course unit, of mapping and visualizing the dependencies between taught concepts and coursework, enabling the inference of new knowledge. The Gamified Educational Learning Contents Ontology (GELCO) was designed to define educational concepts and respective relations. A Syllabus Content Mindmap was developed within the Learning Scorecard, an academic performance management platform based on Business Intelligence and Gamification, taking advantage of the knowledge from GELCO. The ontology was successfully evaluated with competency questions, and students found the mindmap visualization useful and valuable for their academic performance monitoring.